2017
DOI: 10.2965/jwet.17-015
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method to Estimate Influent Concentration Using On-site Lab-scale Activated Sludge Reactors

Abstract: Conventional wastewater analysis based on on-site sampling holds a limitation of accuracy because of fluctuation of influent composition in time and its corruptible nature in organics. To cope with the problem, this study aimed at developing an alternative method using on-site lab-scale activated sludge reactors, where a set of mean influent material concentrations was calculated from the analysis of activated sludge constituents of which fluctuation was damped due to long sludge retention time. Focusing on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…For the reason that temperature was an influencing factor on microbial kinetics [17], the b OHO and µ max_NAO were normalized at 20°C with the temperature coefficient θ OHO (20°C) = 1.029 and θ NAO (20°C) = 1.072 [7,19], leading to b OHO (20°C) = 0.169 1/d and µ max_NAO (20°C) = 0.402 1/d respectively. These obtained kinetic parameter values from the batch experiments seemed to be comparable to those in literature [6,7,11,20]. The probable ranges of specific decay and specific growth rate after normalization at 20°C were respectively calculated as b OHO (20°C) ≈ 0.150~0.188 1/d and µ max_NAO (20°C) ≈ 0.369~0.435 1/d.…”
Section: Kinetic Parameters and Concentration Of Heterotrophic And Ausupporting
confidence: 85%
See 2 more Smart Citations
“…For the reason that temperature was an influencing factor on microbial kinetics [17], the b OHO and µ max_NAO were normalized at 20°C with the temperature coefficient θ OHO (20°C) = 1.029 and θ NAO (20°C) = 1.072 [7,19], leading to b OHO (20°C) = 0.169 1/d and µ max_NAO (20°C) = 0.402 1/d respectively. These obtained kinetic parameter values from the batch experiments seemed to be comparable to those in literature [6,7,11,20]. The probable ranges of specific decay and specific growth rate after normalization at 20°C were respectively calculated as b OHO (20°C) ≈ 0.150~0.188 1/d and µ max_NAO (20°C) ≈ 0.369~0.435 1/d.…”
Section: Kinetic Parameters and Concentration Of Heterotrophic And Ausupporting
confidence: 85%
“…According to recommendation from CH2 M Gore and Storrie Ltd [22], an installation of an auto-sampler equipped with refrigerator was required when performing on-site water sampling. In addition, Nguyen [6] also pointed out that total organic carbon concentration in the municipal wastewater was decreased by 20-30% after 2-day storage at 4°C, therefore daily sampling might be required even availability of 1-day delivering at the experimental site.…”
Section: Possibility Of the Alternative Methods And Further Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in the introduction section, the continuous operation of the field-test activated sludge reactor(s) equipped with DO and nitrate sensors was needed to estimate the dynamic change of influent oxygen demand (biodegradable substances) together with off-line batch analysis to measure the kinetics and biomass concentration in the reactors. The datasets obtained from the field experiments were dynamically analysed in the IWA-Activated Sludge Model #1 (ASM1) to perform the back-calculation for the influent characterisation [12,14]. From the numerical calculation, the estimated concentrations of biodegradable substances were expressed in a discrete form (discrete concentration in every 1-hour).…”
Section: Experimental and Analytical Approachesmentioning
confidence: 99%
“…When the dynamic responses are recorded as the system outputs, the system inputs (influent) can be mathematically obtained using the ASMs in an inverse manner. Using the method Nguyen Duong et al (2017) successfully demonstrated to obtain the ASM-based weeklyaverage influent concentrations from the analysis of activated sludge fractions (dynamic changes of heterotrophic/ autotrophic biomass and unbiodegradable organic particulates during the 7 days) [12]. Unfortunately, their approach is not possible to estimate the hourly influent concentrations because the increment/decrement of the bacterial fractions within 1-hour are too small to be identified.…”
Section: Introductionmentioning
confidence: 99%